Psychological contract, internal branding and employee turnover in an IT company - Oliveira, A. (2019)
We are living in a time of huge competitiveness, where many institutions fight hard for their survival. Unemployment, exclusion, xenophobia, poverty and disrespect towards nature and our peers are causing unbearable impact to humanity. This situation is challenging us to retrieve and keep alive the true values, without any distinction of cultures, religions and ways of thinking. Only this way we can contribute to a fairer, inclusive and better society. A corporation can contribute to the employees' wellbeing, personal and professional fulfillment. The present study is focused in the employee turnover and how it is affected by the internal branding and the psychological contract, in a company of informatic services – in which we mainly considered its organization and human resources. So, we aimed to contribute to the understanding of: internal branding and psychological contract, and their interrelation; effects of internal branding and psychological contract in employees; the turnover (common in this company of informatics services). A questionnaire was developed to measure the internal branding and employees' psychological contract. We used several statistical techniques to analyze the data, namely, descriptive statistics analysis, factorial analysis in principal components, comparison of means and correlations among the resulting dimensions. Findings reveal low values for the internal branding and psychological contract, although, men feel slightly more satisfied with their situation than women. A positive association was found between the internal branding and the psychological contract, admitted as a possible cause of turnover. Anyway, results denote an insufficient concern of the company towards its human resources.